Peran Politielen dalam upaya pencegahan Hipothermia pada Masa Transisi Bayi Baru Lahir - hanna harnida; Emiliana Luh Damayanti (2021)
Public health centres (Puskesmas) are one of the most important health service facilities for people in Indonesia, therefore it is important to improve the access of communities towards good quality health services, including access to basic health services. The service quality of Public health centres must stem from the needs and expectations of the general public. Parasuraman et al identified 5 components in service quality, namely: Tangiblity, Reliability, Responsiveness, Assurance and Emphaty. The purpose of this study was to determine the factors associated with the perception of outpatients towards the service quality at Cilegon. The sample for this study were patients who underwent treatment in the Public Health Centers, aged ≥ 17 years, and as many as 258 respondents. The results of the study showed a proportion of 46.1% who had a good perception towards the quality of outpatient services at the Cilegon Community Health Center. Univariate analysis showed a proportion of 44.2% who had a good perception in the physical evidence component, a proportion of 74% who had a good perception in the reliability component, a proportion of 76.7% who had a good perception in the responsiveness component, a proportion of 78.7% who had a good perception in the assurance component and a proportion of 81.8% who had a good perception in the empathy component. Bivariate analysis found a relationship between internal factors and the perception of the health service quality, namely interest (p = 0.005, PR = 4.138), expectation (p = 0.005, PR = 9.301), and knowledge (p = 0.005, PR = 6.89). The most dominant factor related to perception is expectation.